Estimating the effects of the ADA Amendments Act on the hiring and termination of individuals with disabilities, using new disability categorizations - Patrick Button; Philip Armour; Simon Hollands (W.E. Upjohn Institute for Employment Research, 2023)
Disability discrimination laws are often used to potentially increase employment for individuals with disabilities. However, legal theory and empirical economics research do not provide conclusive answers as to how expansions in disability discrimination laws affect economic outcomes, namely hiring rates, for individuals with disabilities. We estimate the effect of the ADA Amendments Act (ADAAA) on employment transitions: hirings and terminations for individuals with disabilities relative to those without disabilities. To calculate employment transitions, we use data from the Survey of Income and Program Participation (SIPP). We also use the SIPP to develop additional measures and categorizations of disability based on whether the conditions are physical or mental, and whether they are salient to an employer at the hiring stage. We find that the ADAAA is generally associated with positive employment effects: increases or no effects on hiring rates, and decreases or no effects on termination rates. Our strongest and most robust results are that we find increases in hiring for those with nonsalient physical conditions and decreased terminations for those with salient physical conditions. Our results suggest that the effects of the ADAAA vary by disability type-especially by disability saliency-and are stronger for the groups most targeted by broader coverage of the ADAAA.
Keywords: J71; J78; K31; J14; 330; disability; employment discrimination; discrimination law; Americans with Disabilities Act; Americans with Disabilities Amendments Act; Sutton Trilogy